An Introduction and a Critical Look at Metaphor: A Practical Introduction - Fatemeh Rakei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book Metaphor: A Practical Introduction by Zoltán KÖvecses is one of the multi-purpose sources to show the meaning of metaphor. The 2nd edition of the book was published in 2010 by Oxford University. Ms. Shirin Poor Ebrahim has translated the 2nd edition in 2014, which has been published by the Organization for Researching and Composing University textbooks in the Humanities (SAMT Publications). The present research has been done to introduce and study the translated text from various views. In this study, at first, the original version and its translation have been introduced, and the specifications of the translated book with regard to its original versions are studied both from the view of structure and content. The study shows that the translated text as a whole is praiseworthy, and the translator has translated the text attentively and patiently, and the outcome is fluent. Nevertheless, some points about the Persian text are worth to be mentioned. In the present article, the critic has studied the various aspects of the translated book and has proposed some suggestions to be employed in the second edition.